Evaluation of the tight oil "sweet spot" in the Middle Permian Lucaogou Formation (Jimusaer Sag, Junggar Basin, NW China): Insights from organic petrology and geochemistry. (March 2023) - Liu, Shiju; Misch, David; Gang, Wenzhe; Li, Jie; Jin, Jun; Duan, Yanjuan; Xiang, Baoli; Gao, Gang; Zhang, Youjin; Wang, Ming; Fan, Keting
Highlights: Sedimentary conditions in the Lucaogou Formation source rocks are described. The telalginite generated hydrocarbons earlier than the lamalginite. New parameter index to identify effective source rocks is proposed. Abstract: The Middle Permian Lucaogou Formation in the Jimusaer Sag is a hotspot for exploring and developing lacustrine tight oil in the Junggar Basin, NW China. In this study, we evaluated the tight oil potential from the perspective of source rock hydrocarbon generation and expulsion. Based on a detailed organic, petrological, and geochemical characterization of the target interval within the key well JHBE, kinetic experiments were performed on representative shale samples from the well JHBE and the threshold of hydrocarbon expulsion of the source rock was established. The findings of this study revealed that the Lucaogou Formation shales were deposited in a dysoxic to anoxic and clay-poor lacustrine environment with variable salinity and their organic matter (OM) was contributed from both lamalginite and telalginite with minor vitrinite and inertinite, resulting in good to excellent source rock potential. The lamalginite was deposited in water with low salinity, whereas the telalginite developed in water with relatively higher salinity. Although the greater contribution of lamalginite resulted in a higher OM content than that of telalginite, the former generated a lower amount of hydrocarbons than the latter, because telalginite is capable of generating hydrocarbons earlier than lamalginite, which is indicated by the higher HCI (Hydrocarbon index, S1 × 100/TOC), EOM/TOC (extraction of organic matter/total organic carbon), C29 ββ/(αα + ββ), and C29 ααα20S/(20S + 20R) sterane values for telalginite than for lamalginite and is also evident from the difference in activation energy distributions between lamalginite and telalginite source rocks. As determined from the relationships of sterane maturity parameters C29 ββ/(αα + ββ) and C29 ααα20S/(20S + 20R) vs EOM/TOC ratio and HCI values, the lower C29 ββ/(αα + ββ) and C29 ααα20S/(20S + 20R) limits for active source rocks were approximately 0.28 and 0.44, respectively.